2009
DOI: 10.1007/s10900-009-9217-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Covering Health Disparities in Local News Media: An Exploratory Analysis Assessing Views of Journalists

Abstract: News coverage of health topics influences knowledge, attitudes, and behaviors at the individual level, and agendas and actions at the institutional and policy levels. Because disparities in health often are the result of social inequalities that require community-level or policy-level solutions, news stories employing a health disparities news frame may contribute to agenda-setting among opinion leaders and policymakers and lead to policy efforts aimed at reducing health disparities. This study objective was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…As the ratio of public relations workers to journalists has grown significantly as newsrooms have cut staffers (Pew Research Center, 2013;Sullivan, 2011), commercial entities are having increasing success in getting their persuasive messages into the press (Pew Research Center, 2013). Due to the complex nature of health and medical related topics, coupled with overworked health journalists who lack specialized medical training (Corbett, 1998;Corbett & Mori, 1999;Schwitzer, 2009;Tanner, 2004;Wallington et al, 2010a;Wallington et al, 2010b), the current study suggests that local television journalists are increasingly becoming marketers for local hospitals instead of investigators who inform and interpret information and function as independent ''watchdogs'' for the communities they serve (Craft & Davis, 2013;Kovach & Rosentiel, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As the ratio of public relations workers to journalists has grown significantly as newsrooms have cut staffers (Pew Research Center, 2013;Sullivan, 2011), commercial entities are having increasing success in getting their persuasive messages into the press (Pew Research Center, 2013). Due to the complex nature of health and medical related topics, coupled with overworked health journalists who lack specialized medical training (Corbett, 1998;Corbett & Mori, 1999;Schwitzer, 2009;Tanner, 2004;Wallington et al, 2010a;Wallington et al, 2010b), the current study suggests that local television journalists are increasingly becoming marketers for local hospitals instead of investigators who inform and interpret information and function as independent ''watchdogs'' for the communities they serve (Craft & Davis, 2013;Kovach & Rosentiel, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Lindlof and Taylor (2002) note that journalists are good subjects for in-depth interview research because they have specialized knowledge of the field and reflectively communicate their experiences. As such, communication researchers often use journalist interviews to explore a wide-range of media-related topics (Attfield & Dowell, 2003;Besley & McComas, 2007;Besley & Roberts, 2010aTanner, Forde, Besley, & Weir, 2012), including health communication (Hinnant & LenRios, 2009;Wallington, Blake, Taylor-Clark, & Viswanath, 2010b). The current study employed a purposive sampling technique to select 15 to 20 local television news health journalists in the US to participate in in-depth, semi-structured interviews aimed at examining their perceptions related to their health news practices and factors that influence them to generate ideas for health news content and then develop and cover a particular topic.…”
Section: Construction Of Health Newsmentioning
confidence: 99%
“…Producing localized content can be challenging for a local media organization's budget (28), and thus researchers have called for national subsidies to support such coverage for critical topics like health promotion (47, 50). Until such time as subsidies are available, CBOs and local journalists must work together to advance the health of their communities by integrating disparities/SDH content into routine health coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Future research should pay greater attention to the localization elements given their importance in increasing story relevance and mobilizing communities to action. Last, even if greater disparities/SDH coverage is included in local print news—indeed, some journalists have worried about the palatability of such content (47)—there may be other barriers to generating support for structural solutions to disparities. For example, studies have found of evidence of public resistance to disparities messages, particularly along political ideological lines (48).…”
Section: Discussionmentioning
confidence: 99%
“…Public opinion studies show that conservatives are less likely to recognize health disparities than liberals (Booske, Robert, & Rohan, 2011), that the public is more aware of differences in health by socioeconomic status than by race , and that the public judges behavioral factors as more important determinants than social and economic factors . Research also demonstrates that journalists face challenges in covering the issue of health disparities (Wallington, Blake, Taylor-Clark, & Viswanath, 2010), but when they do, they tend to emphasize individual-level behavioral explanations for racial health differences (Kim, Kumanyika, Shive, Igweatu, & Kim, 2010). The emphasis on behavioral factors among the lay public and journalists alike makes sense, given the centrality of personal responsibility in American political thought in general and in health policy discourse in particular (Brownell et al, 2010;Leichter, 2003;Wikler, 2002).…”
Section: Values and Resistance In Health Disparities Communicationmentioning
confidence: 99%